Development of tetra-primer allele specific PCR (tetra-primer AS-PCR) for the detection of L1014F mutation in sodium channel gene associated with pyrethroid resistance in mosquito Culex quinquefasciatus - Chamnanya, Saowanee; Somboon, Pradya; Lumjuan, Nongkran; Yanola, Jintana (Journal of Associated Medical Sciences, 2016)
<p style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px;">Introduction: Extensive use of insecticides in both agriculture and public health pest control has led to resistance of several mosquito species and other insects. Culex quinquefasciatus, an important mosquito vector of urban Bancroftian filariasis, has been reported to be resistant to pyrethroid insecticides in several countries including Thailand. Knockdown resistance (kdr) to pyrethorid in the Cx. quinquefasciatus is usually associated with L1014F mutation in sodium channel gene. Objectives: To develop the tetra-primer allele specific PCR (tetra-primer AS-PCR) assay for detection of L1014F mutation in Cx. quinquefasciatus and to compare the sensitivity and specificity of this assay with DNA sequencing method. Materials and methods: The deltamethrin resistant Cx. quinquefasciatus (Cq_CM_R) mosquitoes were extracted and used as a DNA template for the optimization of tetra-primer AS-PCR assay. PCR amplification of sodium channel gene and DNA sequencing were performed. Genotyping results of L1014F mutation for laboratory and wild-caught Cx. quinquefasciatus mosquitoes obtained from the tetra-primer AS-PCR and DNA sequencing methods were compared. Results: Tetra-primer AS-PCR method was successfully developed to detect L1014F mutation. Testing of 136 laboratory and wild-caught Cx. quinquefasciatus mosquitoes, the developed assay provided the genotyping results consistent with DNA sequencing. Sensitivity and specificity of tetra-primer AS-PCR method were comparable to those of DNA sequencing method. <p style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px;">Conclusion: Developed tetra-primer AS-PCR assay is a simple PCR-based method with high sensitivity and specificity to detect L1014F mutation in Cx. quinquefasciatus mosquitoes. This assay is useful for rapid detection of L1014F mutation which is essential for monitoring resistance to pyrethorid in vector control program. Bull Chiang Mai Assoc Med Sci 2016; 49(2): 389-399. Doi: 10.14456/jams.2016.29